Areal bone mineral density, trabecular bone score and 3D-DXA analysis of proximal femur in psoriatic disease - Toussirot, Eric; Winzenrieth, Renaud; Aubin, François; Wendling, Daniel; Vauchy, Charline; Desmarets, Maxime (Frontiers in Medicine, 2024)
Objectives To evaluate bone mineral density (BMD) and bone quality, with assessment of the cortical and trabecular compartments, in patients with psoriasis (PsO) alone or with psoriatic arthritis (PsA). Methods Patients with PsA and patients with PsO alone were evaluated and compared to control subjects matched for age, sex and body mass index category. Areal BMD (aBMD) was determined for the lumbar spine, femoral neck, total hip and total body using dual-energy X-ray absorptiometry (DXA). Bone quality was evaluated by using trabecular bone score (TBS) at the lumbar spine, and by 3D DXA-based analysis (3D Shaper) for the proximal femur. Results One hundred ninety-six subjects including 52 patients with PsA and 52 patients with PsO and their respective paired controls were analyzed. Patients with PsA had comparable aBMD, TBS and 3D DXA analysis parameters compared to their paired controls. After adjustment for confounders, patients with PsO alone were characterized by a higher aBMD at the left femur and higher cortical 3D DXA derived parameters (total hip cortical surface BMD and total hip cortical thickness) than their paired controls. TBS was decreased in PsO compared to their controls. Conclusion Patients with PsA had normal bone mass and bone quality parameters. Patients with PsO were characterized by higher femoral neck bone density by DXA and cortical parameters by 3D DXA-based analysis, supporting no increased risk for hip fracture. Conversely, bone texture by TBS assessment was decreased in patients with PsO, which may be associated with impaired vertebral bone resistance.